Collateral Crises - Gorton, Gary; Ordoñez, Guillermo (American Economic Review, 2014)
Short-term collateralized debt, private money, is efficient if agents are willing to lend without producing costly information about the collateral backing the debt. When the economy relies on such informationally insensitive debt, firms with low quality collateral can borrow, generating a credit boom and an increase in output. Financial fragility is endogenous; it builds up over time as information about counterparties decays. A crisis occurs when a ( possibly small) shock causes agents to suddenly have incentives to produce information, leading to a decline in output. A social planner would produce more information than private agents but would not always want to eliminate fragility. (JEL D83, E23, E32, E44, G01)